Surgical Scar Site Recurrence in Patients With Cervical Cancer on 18F-FDG PET-CT: A Case-Control Study. Issue 2 (1st February 2016) - Kumar, Sunesh; Dhull, Varun S.; Khangembam, Bangkim C.; Sharma, Punit; Rana, Neelima; Verma, Satyavrat; Sharma, Dayanand; Shamim, Shamim A.; Kumar, Rakesh
Abstract : Purpose: The purpose of this study was to assess the role of fluorine 18 ( 18 F)-fluorodeoxyglucose positron emission tomography-computed tomography ( 18 F-FDG PET-CT) in evaluating various parameters in patients with surgical scar site recurrence in cervical carcinoma. Methods: Data of all patients with cervical cancer (n = 329) who underwent PET-CT at our institute between 2005 and 2013 was reviewed. Of these 329 patients, 132 patients who were surgically treated and underwent restaging/follow-up PET-CT were included in the present study for final analysis. Tumor recurrence at the abdominal surgical scar site was looked for. Abnormal uptakes suggestive of active disease at other sites were also noted. Maximum standardized uptake value was measured for all the lesions. Patients with scar site recurrence were taken as cases (n = 6), whereas the remaining patients served as controls (n = 126). Comparison with conventional imaging modalities was made wherever available. Histopathological examination was always sought for. Results: The incidence of scar site recurrence after surgery was found to be 4.5% (6/117). A total of 56 of 132 patients had recurrent disease, including 6 patients with scar site recurrence. All of the patients with scar site recurrence also had recurrent disease at other sites (local, nodal, or distant). Conventional imaging modalities were available in 4 of these 6 patients and detected scar site recurrence in 3 of those 4 patients. In patients with scar site recurrence, the mean ± SD time to scar site recurrence was 14.0 ± 10.9 months (median, 10 months; range, 7–36 months). Significant difference was seen between cases and control for International Federation of Genecology and Oncology stage ( P = 0.001) and nodal recurrence ( P = 0.007). Additionally, age, nodal recurrence, distant recurrence, and scar site recurrence were significantly associated with death. Conclusions: Scar site recurrence carries a poor prognosis, and the incidence is much higher than previously known when PET-CT is used as a modality for its detection.